A rapid gas chromatography tandem mass spectrometry method for the determination of 50 PAHs for application in a marine environment. Issue 46 (14th November 2018) - Park, Grace; Brunswick, Pamela; Kwok, Honoria; Haberl, Maxine; Yan, Jeffrey; MacInnis, Ceara; Kim, Marcus; Helbing, Caren; van Aggelen, Graham; Shang, Dayue
Abstract : A micro-extraction gas chromatography pseudo-MRM mass spectrometry method was developed for the rapid determination of 50 selected PAHs and APAHs in seawater. Abstract : A micro-extraction gas chromatography pseudo-MRM mass spectrometry method was developed for the rapid determination of 50 selected polycyclic aromatic hydrocarbons (PAHs) and alkylated-PAHs (APAHs) in seawater. The combined PAHs and APAHs, referred to as total polycyclic aromatic hydrocarbons (TPAHs), include dibenzothiophenes and naphthabenzothiophenes. The method was aimed at the assessment of TPAH compounds in the water accommodated fraction of oil in seawater, now promoted for use in toxicity evaluation following an oil spill incident. The presented method applies a unique multi-level quantitative calibration method for many alkylated PAHs for which the authentic standards are either extremely expensive or difficult to obtain. This new method was able to determine all 50 TPAH compounds while avoiding excessive cost. The reliability of this isotope dilution micro-extraction method was shown by extraction and analysis of Prudhoe Bay oil, with comparable compound results corresponding to published data. The developed method was successfully applied to water accommodated fraction (WAF) samples prepared with Low Sulfur Marine Diesel, High Sulfur Fuel Oil and Diluted Bitumen in seawater. With reduced cost and a single injection for all the 50 target compounds, this rapid quantitative method allows for routine environmental monitoring of a larger suite of TPAH analytes.